(untitled) (Indonesian Journal of Agrarian Law, 2026)
This study was motivated by the dismissal of a civil lawsuit based on the grounds of obscuur libel in a land dispute in Bekasi Regency, which resulted in a third party acting in good faith, Mr. Yealdi, becoming a victim of wrongful execution. The Cikarang District Court Decision No. 82/Pdt.G/2025/PN Ckr dismissed the lawsuit on the grounds that it did not meet the formal clarity of the statement of facts and the prayer for relief, even though the plaintiff held a valid title deed and alleged a violation of land rights. The objective of this study is to analyze the legal validity of the application of obscuur libel from the perspectives of civil procedure law, agrarian law, and the principle of substantive justice, as well as to assess its implications for the protection of the rights of bona fide third parties. Using a legal-normative research method that examines court decisions, legislation, and relevant legal literature, this study found that the rigid application of obscuur libel disregards the dimension of substantive justice and the principle of legal protection for rights holders acting in good faith, as mandated by the UUPA and the Constitution. Such procedural formalism has the potential to hinder access to justice and exacerbate inequalities in the resolution of agrarian disputes. As recommendations, the study proposes strengthening pre-trial mediation mechanisms, adjusting the interpretation of obscuur libel to be more responsive to substantive contexts, and developing judicial guidelines that consider socio-agrarian aspects in the adjudication of land cases.